LIVELIHOOD STRATEGIES IN IMMIGRANT COMMUNITIES OF ORIGIN AMBON IN FULFILLMEN HOUSEHOLDS NEEDS IN THE MASIRI VILLAGE OF BATAUGA BUTON DISTRICT SOUTHEAST SULAWESI PROVINCE - , La Ode Hane, S.Pd, Prof. Dr. H. R. Rijanta, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Income earning strategy is a choice that is formed by asset, access, and activity, and these are influenced by the capacity of a person or household to carry out the combination of activity and options, in order to achieve welfare as a manifestation of better income earning. This research aims to: 1. explore the income earning strategies of migrant community in meeting household needs